Efeito da desintegrina recombinante DisBa-01 incorporada em micelas ou livre em células portando ou não a integrina αvβ3 - Ribeiro, Lívia Carolina de Abreu [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Introduction: integrin αvβ3 sustain cellular adhesion to vitronectin and is expressed on a diversity of human tumors but is present at very low levels on normal tissues, with notable expression on bone marrow-derived cells. The recombinant disintegrin DisBa-01 binds to αvβ3 integrin, inhibiting cell adhesion to vitronectin. It also features an in vivo anti-metastatic ability and in vitro anti-thrombotic function. Micelles are a transport system that can direct a drug to the target tissue passively, accumulating where microvasculature is more permeable, which happens on cancer. Objectives: to verify adhesion loss, mediators production, citotoxicity and anoikis generated by disintegrin DisBa-01, both in its free form or incorporated into micelles, in cell lines expressing or not αvβ3 integrin. Methods: the disintegrin was expressed in Escherichia coli using a cDNA fused to vector pET28a, and then purified by chromatography and dialyses. Control micelles (M-C) or containing disintegrin (M-DB) were assembled using polysorbate 80 and soy phosphatidylcholine, and it was observed the average diameter and polydispersity index by dynamic light scattering, zeta potential by microelectrophoresis, the efficiency of encapsulation by protein determination using Lowry reagent, structural assessment of disintegrin encapsulated by circular dichroism spectroscopy and fluorescence spectroscopy and micelles’ structure by SAXS curve. The protein free or incorporated into micelles were tested in HUVEC and SC, containing integrin αvβ3, and in K562, not containing this integrin. Cytotoxicity was evaluated by MTT assay, inhibition of cell adhesion and detachment to vitronectin or fibronectin by quantifying the adherent cells with crystal violet, the anoikis by observation of viable cells and apoptosis, whether attached or not, by MTT, Apo-Direct and annexin V, and production of mediators VEGF-A, IL-8, TGF-β, TNF-α, IL-12 and ...

Introdução: a integrina αvβ3 causa adesão celular à vitronectina e está expressa em diversos tumores humanos, mas está em níveis muito reduzidos nos tecidos normais, sendo mais notável em células derivadas da medula óssea. A desintegrina recombinante DisBa-01 se liga à integrina αvβ3, inibindo a adesão celular à vitronectina. Apresenta também uma capacidade antimetastática in vivo e antitrombótica in vitro. As micelas são sistemas de transporte que podem direcionar o fármaco ao tecido alvo de forma passiva, se acumulando onde a microvasculatura esteja mais permeável, como no caso do câncer. Objetivos: verificar a perda de adesão, a liberação de mediadores, a citotoxicidade e a anoikis gerados pela desintegrina DisBa-01, tanto em sua forma livre como incorporada em micelas, em linhagens celulares que expressem ou não a integrina αvβ3. Métodos: a desintegrina foi expressa em bactérias Escherichia coli a partir de um cDNA fusionado ao vetor pET28a, e então purificada por cromatografias e diálises. As micelas controle (M-C) ou contendo a desintegrina (M-DB) foram estruturadas com polissorbato 80 e fosfatidilcolina de soja, e foi observado o diâmetro médio e índice de polidispersidade por espalhamento dinâmico de luz, o potencial zeta por microeletroforese, a eficiência de encapsulação por dosagem protéica de Lowry, a avaliação estrutural da desintegrina encapsulada por espectroscopias de dicroísmo circular e de fluorescência e a estrutura das micelas pela curva de SAXS. As micelas e a proteína livre foram testadas em linhagens HUVEC e SC, contendo a integrina αvβ3, e K562, não contendo esta integrina. Foram avaliados a citotoxicidade pelo teste de MTT, a inibição de adesão celular ou descolamento a vitronectina e fibronectina por quantificação das células aderidas com cristal violeta, a anoikis por observação das células viáveis e em apoptose se aderidas ou não por MTT, Apo-Direct ...
Keywords: Micelas; Cancer; Celulas da medula ossea; Citotoxicidade; Micelles